Estágio supervisionado: proposta de intervenção no 5º ano do ensino fundamental em uma escola municipal de Belém-Pa - MORAES, Maria Eliana de Souza (2020)
The purpose of this paper is to report an experience that occurred during a mandatory supervised internship, in which I had the opportunity to apply the project “Açaí: Essence of the culture from Pará”, as a proposal of teaching practice with a class from the fifth grade of a public city elementary school. The text is organized as follows: introduction, characterization of the school where the project was carried out, pedagogical work developed by the conducting teacher, organization of the classroom physical environment, available teaching materials, observation of teaching practice, activities developed during the internship and pedagogical practices, part in which the accomplishment of the mentioned project will be reported. The conclusions reached were as follows: which Açaí project: essence of the Amazonian culture of an interdisciplinary nature aimed to unite the approach of regional themes, close to the student's reality to the didactic content. The choice of the theme “açaí” is due to the fact This is part of the identity and culture of Para. Acai is material culture and, at the same time, immaterial culture through myths, narratives and legends. It is an identity-forming element, anthropologically understood as "self-recognition" as opposed to otherness, which refers to "recognition of the other." The work with the Açaí, both as a resource and a research\teaching-learning theme, was valuable as an internship practice, and surpassed expectations in presenting to the school the importance of integrated planning and the pleasure of teamwork facing the reality experienced by the teachers and students of the referred school, which needed, in their teaching and studying lives, experiences that would involve them in a formation for sustainable citizenship, based on scientific research and the strengthening of paraense culture.